HARMONIZATION OF STATE ADMINISTRATION: ANALYSIS OF PUBLIC SERVICES IN THE CONCEPT OF GOOD GOVERNANCE - Irfansyah (Adisam Publisher, 2025)
Harmonization of state administration and analysis of public services in the concept of good governance are very relevant topics in the context of public administration reform in many countries. Good governance emphasizes the importance of transparency, accountability, public participation, good rule of law, as well as efficiency and effectiveness in administering government. Harmonization of state administration refers to efforts to align various components of public administration so that they work efficiently and effectively in achieving government goals. This includes good coordination between government agencies, clear division of tasks, and integration of administrative processes to avoid overlap and promote optimal use of resources. Implementing the concept of good governance in public services requires commitment from the government and related parties to carry out reforms in the public administration system. This includes developing policies that support transparency and accountability, increasing the ability of institutions to provide quality services, and increasing community participation in decision making. Although the concepts of good governance and harmonization of state administration offer a strong framework for improving public service performance, their implementation is often faced with challenges such as corruption, lack of resources, and resistance to change from the parties involved. However, with a strong commitment from all relevant parties, it can be hoped that public administration reform can produce better, more efficient and more inclusive public services for all citizens.